Desenvolvimento de um circuito em Handel-C para experiências com máquinas de estados finitos - Arrais, Joel (2003)
This paper describes an FPGA-based circuit, which permits to specify and to simulate finite state machines (Moore model). Interaction with the circuit is provided through a graphical interface designed for a VGA monitor with the relevant support for a mouse and a keyboard. Functionality of the circuit was described in Handel-C, which is a system-level specification language developed by Celoxica. The Handel-C description wasverified in Celoxica DK1 environment and compiled to an EDIF file. The latter was used as an input for ISE 5.2 software, which generated a bitstream for an FPGA. The designed circuit was tested in the RC100 prototyping board of Celoxica that contains an FPGA XC2S200 of Spartan-II family of Xilinx.